The mechanism of concession agreements in the Russian heat supply system - A. G. Zakrevskaya; N. G. Lyubimova; A. S. Flaxman (Вестник университета)
The current research examines the mechanism of concession agreements, functioning in the sphere of heat supply, the ways of its conclusion, its advantages and differences from lease agreements. The effectiveness of the use of concessions is proved on the example of Voronezh and Perm energy companies. The renewal of the Russian heat supply system is, unfortunately, extremely slow. Despite the measures taken, the dynamics of equipment failures, accidents and heat losses have not yet been changed: their number is still gro wing. In a year, it is possible to update only half of the fixed assets from the need. The reasons for this are their sharp moral and physical ageing and lack of investors who would finance reconstruction, modernisation and erection of new heating system objects. The owners of the systems in many Russian regions are municipalities whose budget funds are insufficient to upgrade them. Mechanisms of public-private partnership (concession agreements are one of its manifestations) together with the “alternative boiler house” mo del should contribute to rectifying the situation. However, unconscientiousness of some investors, the failure to fulfill their obligations for construction and reconstruction of heat supply systems question the effectiveness of the mechanism and reduces them to lease agreements involving only operation of leased worn equipment. According to the research, the authors concluded that it is necessary to improve the discussed mechanism, monitor implementation of the agreements and strengthen administrative responsibility for non-compliance.